Cortical Activation during Action Observation, Action Execution, and Interpersonal Synchrony in Adults: A functional Near-Infrared Spectroscopy (fNIRS) Study - Bhat, Anjana N.; Hoffman, Michael D.; Trost, Susanna L.; Culotta, McKenzie L.; Eilbott, Jeffrey; Tsuzuki, Daisuke; Pelphrey, Kevin A. (Frontiers in Human Neuroscience, 2017)
Humans engage in Interpersonal Synchrony (IPS) as they synchronize their own actions with that of a social partner over time. When humans engage in imitation/IPS behaviors multiple regions in the frontal, temporal, and parietal cortices are activated including the putative Mirror Neuron Systems (Iacoboni, 2005; Buxbaum et al., 2014). In the present study, we compared fNIRS-based cortical activation patterns across three conditions of action observation (“Watch” partner) or, action execution (“Do” on your own), and IPS (move “Together”). Methods: 15 typically developing adults completed a reach and cleanup task with the right arm while cortical activation was examined using a 24-channel, Hitachi fNIRS system. Each adult completed 8 trials across three conditions (Watch, Do, and Together). For each fNIRS channel, we obtained oxy hemoglobin (HbO2) and deoxy hemoglobin (HHb) profiles. Spatial registration methods were applied to localize the cortical regions underneath each channel and to define six regions of interest (ROIs), right and left supero-anterior (SA or pre/post-central gyri), infero-posterior (IP or angular/supramarginal gyri), and infero-anterior (IA or superior/middle temporal gyri) regions. Results: In terms of task-related differences, the majority of the ROIs were more active during Do and Together compared to Watch. Only the right/ipsilateral fronto-parietal and inferior parietal cortices had greater activation during Together compared to Do. Conclusions: The similarities in cortical activation between action execution and IPS suggest that neural control of IPS is more similar to its execution than observational aspects. For example, the more complex the actions performed, the more difficult the IPS behaviors. Secondly, IPS behaviors required slightly more right-sided activation (vs. execution/observation) suggesting that IPS is a higher-order process involving more bilateral activation compared to its sub-components. These findings provide a neuroimaging framework to study imitation and IPS impairments in special populations such as infants at risk for and children with ASD.